ANALYZING RAGHU RAI’S PHOTOGRAPHIC EXPEDITION AND CULTURAL HERITAGE PRESERVATION IN INDIA - C P, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For many years, famous photographer Raghu Rai has used his camera to capture the spirit of India. His work has received widespread acclaim for its artistry, originality, and capacity to convey the nation’s rich, varied cultural past. The goal of this analysis is to shed light on Raghu Rai’s photographic journey and examine the major topics and motifs that characterize his distinctive aesthetic. In the study, Raghu Rai’s efforts to safeguard India’s cultural heritage for future generations are also emphasized. The study consults a variety of sources, such as the photographer’s interviews, reviews of his work, and pertinent academic literature. This review highlights Raghu Rai’s contributions to the field of photography as well as his work to protect and advance India’s cultural heritage for future generations. Raghu Rai’s distinctive aesthetic is marked by his keen eye for capturing the essence of Indian culture and traditions. His photographs often depict the vibrancy and diversity of the country, showcasing its rich heritage and timeless beauty. Through his work, Rai not only documents India’s cultural legacy but also plays a crucial role in preserving it for future generations to appreciate and cherish. By highlighting Rai’s significant contributions to photography and the preservation of India’s cultural heritage, this study honors his tireless efforts to protect the country’s cultural heritage.